PENGARUH PEMURIDAN REMAJA USIA 13-18 TAHUN TERHADAP PERTUMBUHAN JUMLAH KEHADIRAN REMAJA DI IBADAH JUNIOR CHURCH DI GBI TABGHA BATAM - Andre Djaafar; Gomgom Purba; Suhendra; Cresty Agustina (JURNAL IMPARTA, 2023)
Discipleship teenager’s is very essential for the growth of teenager’s attendance which does not affect the spiritual life but also outwardly, the phenomenon of declining discipleship is feared to also have a negative impact on the growth of teenager’s attendance in worship. This study aims to determine how much influence discipleship teenager’s directly have on the growth of church attendance. This study uses quantitative methods based on quantification in data collection and analysis to test the established hypotheses. Conducted at the Junior Church of Bethel Church Indonesia Tabgha Batam, from October 2021 to May 2022. The results of the research prove that the level of (1) understanding of the benefits of discipleship is in the range 176.80-185.375: moderate to high class, (2) the growth rate of attendance is in the range of 144.68-151.36: high class. This study also found (3) The contribution of the influence of discipleship partially to the growth of church attendance was 76.9%. The magnitude of the direct influence of the Discipleship teenager’s aged thirteen to eighteen year’s variable on the growth of church attendance is 24,066, meaning that if the Discipleship teenager’s (X) is 0, then the growth of church attendance (Y) Junior Church of Bethel Church Indonesia Tabgha Batam the value is 24,066 units. The regression coefficient of the Discipleship teenager’s variable (X) is 0.685; This means that if the Discipleship teenager’s is increased by one time, it will increase the growth of church attendance (Y) by 0.685.